PENERAPAN MODEL QUANTUM LEARNING TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS XI IPA DI SMA NEGERI 3 KOTA SOLOK - Resita, Shintia - (Pendidikan Biologi, 2014)
This study is based on the low of student class XI IPA SMA N 3 Solok in Biology subject. It iscaused by some factors. For example teacher prefers to use speech methode in teaching learningprocess. Beside that, teacher as provider of information prefers to dominate learning activities inclassroom, so that there is an interaction between teacher and the student, but less interaction amongstudents. It is implicated to the quality of learning and cause the learning be boring. The purpose ofthis reseach is to know whether the implementation of Quantum Learning model can improvestudents outcomes in material that discuss about regulatory system SMA N 3 Solok academic year2014/2015. Kind of this reseach is an experimental study with Randomized Control Group PostestOnly Design. Study population is all of students class XI IPA in SMA N 3 Solok academic year2013/2014. Sampling technique is purposive sampling. The average of test result is 79, 41 foreksperimental class student and 65,33 for control class. Based on hypothesis test result by using-ttest obtained t calculate > t tabel that is 3,84 > 1,67. It can concluded that studying biology by theapplication of model quantum learning can improve students outcomes class XI IPA in SMA N 3Solok.